System‐dependent image distortion related to gantry positions of a 0.35 T MRgRT: Characterization and the corresponding correction. Issue 1 (10th November 2022) - Marasini, Shanti; Quinn, Benjamin; Cole, Mike; Flores, Rocco; Kim, Taeho
Abstract: Purpose: MR‐guided radiotherapy with high accuracy treatment planning requires addressing MR imaging artifacts that originate from system imperfections. This work presents the characterization and corresponding correction of gantry‐related imaging distortions including geometric distortion and isocenter shift in a 0.35 T magnetic resonance imaging (MRI)‐guided radiotherapy (MRgRT) system using distortion vector fields (DVFs). Methods: Two phantoms, the magnetic resonance imaging distortion in 3D (MRID 3D ) phantom and the Fluke phantom, along with a human volunteer were imaged at different gantry angles on a 0.35 T MR‐Linac. The geometric distortion and isocenter shift were characterized for both phantom images. DVFs with a field of view extended beyond the physical boundary of the MRID 3D phantom were extracted from images taken at 30° gantry angle increments, with vendor‐provided distortion correction turned on and off (DstOff). These extended DVFs were then applied to the relevant phantom images to correct their geometric distortions and isocenter shift at the respective gantry angles. The extended DVFs produced from the MRID 3D phantom were also applied to Fluke phantom and human MR images at their respective gantry angles. The resampled images were evaluated using structural similarity index measure (SSIM) comparison with the vendor corrected images from the MRgRT system. Results: Geometric distortion with "mean (± SD) distortion" of 3.2 ± 0.02, 2.9 ± 0.02, and 1.8 ± 0.01 mm and isocenter shift (±SD) of 0.49 ± 0.3, 0.05 ± 0.2, and 0.01 ± 0.03 mm were present in the DstOff MRID 3D phantom images in right–left (RL), anterior–posterior (AP), and superior–inferior (SI) directions, respectively. After resampling the originally acquired images by applying extended DVFs, the distortion was corrected to 0.18 ± 0.02, 0.09 ± 0.01, 0.15 ± 0.01 mm, and isocenter shift was corrected to 0.14 ± 0.05, −0.02 ± 0.04, and −0.07 ± 0.05 mm in RL, AP, and SI directions, respectively. The Fluke phantom average geometric distortion with "mean (± SD) distortion" of 2.7 ± 0.1 mm was corrected to 0.2 ± 0. 1 mm and the average isocenter shift (± SD) of 0.51 ± 0.2 mm, and 0.05 ± 0.03 was corrected to −0.08 ± 0.03 mm, and −0.05 ± 0.01 in RL and AP directions, respectively. SSIM (mean ± SD) of the original images to resampled images was increased from 0.49 ± 0.02 to 0.78 ± 0.01, 0.45 ± 0.02 to 0.75 ± 0.01, and 0.86 ± 0.25 to 0.98 ± 0.08 for MRID 3D phantom, Fluke phantom, and human MR images, respectively, for all the gantry angles compared to the vendor corrected images. Conclusion: The gantry‐related MR imaging distortion including geometric distortion and isocenter shift was characterized and a corresponding correction was demonstrated using extended DVFs on 0.35 T MRgRT system. The characterized gantry‐related isocenter shift can be combined with geometric distortion correction to provide a technique for the correction of the full system‐dependent distortion in an MRgRT system.